QUALITY MANAGEMENT OF TEACHING â€“ LEARNING PROCESS AT THE TECHNICAL UNIVERSITY OF KOÅ ICE (SLOVAKIA) - BlaÅ¡ko, Michal; Raschman, Pavel (European Scientific Journal, ESJ, 2015)
The purpose of this paper is to provide some basic information on the methods applied in the management of quality assurance in the delivery of higher education at the Technical University of KoÅ¡ice. The aim is to present programs and results of the course in the quality management of teaching to ensure the quality of university teachers as one of the areas of the internal quality system of a higher education institution.